Indirect geophysical model of Istrian bauxite deposits - Lapajne, Janez (Geologija, 1979)
The bauxite bodies in Istria lie rather deep and are too small to be directly identified. Bauxite is a common residual constituent found in pockets of Cretaceous limestone. During its formation and compaction, its volume is reduced. Therefore its hanging wall, consisting of Eocene limestone, settles in the Cretaceous pocket. The rents and fissures in the hanging wall are filled with clay. Due to favorable wet conditions this geological structure becomes a low resistivity body, corresponding to a hemispheroid or dike. Resistivity curves over these models fit the corresponding observed resistivity profiles very well, the difference being within a few percent on average. The paper contains a collection of resistivity type curves. With regard to the hemispheroid, there occurs in specific conditions a remarkable paradox: the thinner the hemispheroid, the more significant the anomaly.